Quando a consulta popular é uma fábula - O conto Sereníssima República de Machado de Assis como interpretação da democracia direta na América Latina - de Carvalho, Vinicius Mariano (Diálogos Latinoamericanos, 2011)
Originally published in 1882, in the collection of short-stories Papéis Avulsos, A Sereníssima República has as central theme the description of the political corruption, especially in the electoral context. The story also discusses how an ideal model (e.g. democracy), even if just, can be distorted in different ways, when subjected to practice. Also, the narrative shows all possible tricks of acquisition and retention of power. On the use of different textual resources: it is a tale, with the typical structure of this genre, which tells of a conference of Cônego Vargas that disseminates the scientific discovery about the world of spiders, with all the philosophical and scientific rigor inherent in this type of discourse. At this moment the text acquires the characteristics of a fable. With a distinctive wit and irony, the writer develops a critical reflection about the popular consultation and the consequent irregular political manipulation of this process. On the basis of Machado de Assis‟ story this paper will enlarge the discussion, noting how his story can provide a critical and interpretative key to the interpretation of direct democracy in contemporary Latin America.